Serum Midkine and Osteopontin Levels as Diagnostic Biomarkers of Hepatocellular Carcinoma - Hodeib, Hossam (Electron Physician, 2017)
INTRODUCTION: Hepatocellular Carcinoma (HCC) is a primary tumor of the liver; it is one of the most common cancers worldwide. Osteopontin (OPN) is a phosphorylated glycoprotein which is implicated in enhancing invasive and metastatic progression of many tumors. Midkine (MDK) is a 13-kDa small heparin-binding growth factor which plays a significant role in carcinogenesis related activities. The aim of this study was to assess the efficacy of serum Midkine and Osteopontin levels as diagnostic biomarkers of Hepatocellular Carcinoma. METHODS: This study was carried out from January 2014 to January 2016 in Internal Medicine, Clinical Oncology and Tropical Medicine Departments of Tanta University Hospital (Egypt). One hundred forty subjects were enrolled in our study, they were divided into four groups: Group I included 35 patients presented with HCV without cirrhosis; Group II included 35 patients presented with HCV with liver cirrhosis; Group III included 35 patients presented with HCC on top of cirrhosis; and Group IV included 35 apparently healthy subjects as a control group. The studied groups were age and sex matched. Routine and specific (OPN and MDK) laboratory investigations were performed in all included subjects. RESULTS: The main finding of the present work was that the mean serum levels of OPN and MDK were significantly elevated in HCC patients either by comparing HCC patients vs. HCV patients without cirrhosis, HCC patients vs. HCV patients with cirrhosis or HCC patients vs. healthy subjects. Interestingly, by performing a ROC analysis, serum MDK levels had better sensitivity and specificity than OPN and AFP levels in the diagnosis of HCC (98.4 %, 97.1% and 97%) and (96.2%, 95.3% and 95%) for MDK, OPN and AFP respectively. CONCLUSION: Serum MDK and OPN levels are comparable to AFP levels and could be used as potential diagnostic biomarkers of HCC in HCV patients with liver cirrhosis and in the prediction of liver cirrhosis in HCV patients without cirrhosis.